CHARACTERISTICS OF A GOOD EFL TEACHER: INDONESIAN EFL STUDENTS PERSPECTIVES - Sakkir, Geminastiti; Dollah, Syarifuddin; Ahmad, Jamaluddin (JURNAL NALAR PENDIDIKAN, 2021)
This study aims to ascertain student perceptions of the characteristics of effective EFL teachers. This research is qualitative and quantitative. The subjects in this study were 24 students with 4 male and 20 female students of the fourth semester of English Education Department who were asked about their perceptions of the characteristics of a good EFL teacher. The data analysis technique uses the Miles and Huberman model with stages of data reduction, data visualization, to drawing conclusions/verification. The research instrument is divided into four sections that discuss personal, social, professional, and pedagogical competencies. The results showed that a good EFL teacher should be friendly, have accurate pronunciation, and have practical classroom management skills. In addition, the results of student research indicate that they expect EFL teachers to be enthusiastic about technological advances, while visual materials help them relax during lectures. Based on the results of the research above, it can be concluded that the overall results of the study indicate that student perceptions may differ when considering the characteristics of good EFL teachers in general. The critical nature of both pedagogical and personal characteristics and social competencies that contribute to being an effective and professional teacher, anyone who aspires to be an effective EFL teacher must be fully aware of the role of personality.